2006
DOI: 10.1074/mcp.m600162-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Challenges in Liquid Chromatography-Mass Spectrometry-based Proteomics Profiling for Clinical Applications

Abstract: Recent advances in proteomics technologies provide tremendous opportunities for biomarker-related clinical applications; however, the distinctive characteristics of human biofluids such as the high dynamic range in protein abundances and extreme complexity of the proteomes present tremendous challenges. In this review we summarize recent advances in LC-MS-based proteomics profiling and its applications in clinical proteomics as well as discuss the major challenges associated with implementing these technologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
284
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 327 publications
(294 citation statements)
references
References 121 publications
5
284
0
2
Order By: Relevance
“…14,15 While albumin, the most abundant plasma protein, accounts for ∼60% of the plasma protein weight, this number increases to 96%whenthe12mostabundantplasmaproteinsareconsidered. 14,15 Thus, the discovery of very low abundance glycated proteins represents the proverbial "needle in a haystack".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14,15 While albumin, the most abundant plasma protein, accounts for ∼60% of the plasma protein weight, this number increases to 96%whenthe12mostabundantplasmaproteinsareconsidered. 14,15 Thus, the discovery of very low abundance glycated proteins represents the proverbial "needle in a haystack".…”
Section: Discussionmentioning
confidence: 99%
“…This trend is more apparent for the glycated proteins from whole plasma than for the glycated proteins from the low-abundance protein fraction of plasma (data not shown). A possible explanation for this observation is that low-abundance proteins, which have higher turn-over rates compared with the classical plasma proteins and account for less than 4% of the plasma protein weight, 15 do not accumulate significant amounts of the Amadori compound before in vivo proteolytic digestion. Similarly, the observed quantitative difference (based on HPLCUV) in levels of enriched glycated plasma peptides was not as readily distinguished among the three sample groups as the enrichment on the protein level (data not shown).…”
Section: Bac Enrichment Of Glycated Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In proteomics, diseased tissue samples or proximal fluids are often a more straightforward material for analysis to reach clinically relevant results due to higher analyte concentrations compared to plasma and serum 1,2 which, because of dilution and clearance, carry lower concentration of pertinent proteins. However, it has been shown that, following tissue sampling, substantial alterations of the proteome occurs.…”
Section: Introductionmentioning
confidence: 99%
“…(LC-MS/MS), for greatly improved speed and efficiency. The high throughput and sensitive nature of this technique has made it an increasingly popular approach for (comparative) proteome profiling (Link et al, 1999;Qian et al, 2006).…”
Section: Complementing 2-de: the Emergence Of Non-gel Based Approachesmentioning
confidence: 99%